Low-field electron emission and cathode luminescence of piezoelectric films of oxides and chalcogenides - Dadykin, A.A.; Naumovets, A.G.; Gorbik, P.P.; Dubrovin, I.V.; Ogenko, V.M.; Filonenko, M.N. (Поверхность, 2002)
Basic parameters of effective low-field emitters of electrons of piezoelectric films for bright flat cathode luminescent display and other activity are optimised. Specimens of electron emitters of cathode luminescent screens are based on compounds of SiO₂, ZnO, ZnS, solid solution of Zn1-xCdxS. High efficient "cold" emitters of electrons were prepared on the basis of mono- and polycrystalline films. The emission and cathode-luminescent properties of the films were investigated. It is shown that developed films are perspective like the flat displays with the brightness of 300 Cd/m².